2008
DOI: 10.1002/ana.21430
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive dementia

Abstract: In contrast with more common dementing conditions that typically develop over years, rapidly progressive dementias can develop subacutely over months, weeks, or even days and be quickly fatal. Because many rapidly progressive dementias are treatable, it is paramount to evaluate and diagnose these patients quickly. This review summarizes recent advances in the understanding of the major categories of RPD and outlines efficient approaches to the diagnosis of the various neurodegenerative, toxic-metabolic, infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
278
0
17

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 287 publications
(301 citation statements)
references
References 120 publications
(233 reference statements)
6
278
0
17
Order By: Relevance
“…The neuropathological profile of our series was not different from those previously reported in RPD, except for the high frequency of prion diseases (67%), which was similar to that reported in a previous study also performed in a reference centre for prion disease diagnosis [1]. AD was the second most frequent aetiology, followed by DLB.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The neuropathological profile of our series was not different from those previously reported in RPD, except for the high frequency of prion diseases (67%), which was similar to that reported in a previous study also performed in a reference centre for prion disease diagnosis [1]. AD was the second most frequent aetiology, followed by DLB.…”
Section: Discussionsupporting
confidence: 72%
“…The term ‘rapidly progressive dementia' (RPD) encompasses a heterogeneous group of medical conditions that cause progressive cognitive impairment, leading to functional disability or death within a short period of time, usually less than 24 months [1,2]. Creutzfeldt-Jakob disease (CJD) represents the leading cause of RPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that 62% of all patients had prion disease, and in 38% of the non prion RPD patients, neurodegenerative diseases accounted for 39% of cases, autoimmune for 22%, and unknown cause for 12%. 9 Rapidly progressive neurodegenerative diseases such as Lewy Body Dementia (LBD), Frontal Temporal disease (FTD), and Cortical Basal-ganglia degeneration (CBD), were included our patient's differential diagnoses, due to patient's overall cognitive decline, visual hallucinations, and extra-pyramidal symptoms. Autoimmune encephalitis was also considered, given his acute onset and progression of symptoms, but this was ruled out due to lack of autoimmune antibody index and an ineffective trial of high dose corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most dementing conditions that typically develop over years, rapidly progressive dementia (RPD) being quickly fatal is one of the most challenging problems. The differential diagnosis is often widely ranging, and, in addition to frequent prion diseases includes rapidly progressing neurodegenerative tauopathies and synucleinopathies, autoimmune condition infections, toxic-metabolic and neoplastic diseases (Geschwind et al, 2008;Josephs et al, 2009). According to the US National Prion Disease Pathology Surveillance Center (NPDPSC) in patients with RPD, treatable disorders are frequently mistaken for CJD.…”
Section: Frontotemporal Lobe Degeneration (Ftld)mentioning
confidence: 99%